Determinants of customer satisfaction in e-commerce: a case study in higher learning institutions in Johor / Abd Halim Mohamad and Sabrinah Adam - Mohamad, Abd Halim; Adam, Sabrinah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Customer satisfaction is an essential experience in e-commerce. The objective of this study was to identify determinants of customer satisfaction in e-commerce. This case study adopted its theoretical framework from the Theory of Reasoned Action (TRA). It also applied a quantitative research methodology by using self-administered questionnaires as a measurement tool in gathering sample data. The sample were student’s students from various course backgrounds in higher learning institutions in Johor. A total of 224 students answered the questionnaires. IBM SPSS version 26 was used to analyse the sample data. A test of reliability was carried out using the Cronbach’s alpha method. Later, using Pearson correlation and multiple regression analysis to assess the interrelationship between the independent and dependent variables, predictors and criteria values were identified. The findings revealed that user interface quality, product information quality, security perception, and privacy perception had a positive relationship with customer satisfaction. However, e-service quality had a negative relationship and had no significant impact on customer satisfaction. This study provides insight into the influencing aspects and their functions. This would allow e-commerce firms to improve their websites based on the findings.